Leaf paraheliotropism in Styrax camporum confers increased light use efficiency and advantageous photosynthetic responses rather than photoprotection - Habermann, Gustavo [UNESP]; Ellsworth, Patricia F. V.; Cazoto, Juliana L.; Feistler, Aline M. [UNESP]; da Silva, Leandro; Donatti, Dario A. [UNESP]; Machado, Silvia R. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Styrax caporum is a native shrub from the Brazilian savanna. Most of its leaves are diaheliotropic, whereas some are paraheliotropic, mainly at noon. A previous study of this species revealed higher stomatal conductance (gs) and transpiration rates (E) in para- compared to diaheliotropic leaves, and a rise in CO(2) assimilation rates (A) with an increase of irradiance for paraheliotropic leaves. We hypothesized that this species exploits the paraheliotropism to enhance the light use efficiency, and that it is detected only if gas exchange is measured with light interception by both leaf surfaces. Gas exchange was measured with devices that enabled light interception on only one of the leaf surfaces and with devices that enabled light interception by both leaf surfaces. Water relations, relative reflected light intensity, leaf temperature (T(l)), and leaf anatomical analyses were also performed. When both leaf surfaces were illuminated, a higher A. E, and gs were observed in para- compared to diaheliotropic leaves; however, A did not depend on gs, which did not influence CO(2) accumulation in the stomatal cavity (Ci). When only the adaxial leaf surface was illuminated, a greater A was detected for para- than for diaheliotropic leaves only at 11:00 h; no differences in T(l) were observed between leaf types. Light curves revealed that under non-saturating light the adaxial side of paraheliotropic leaves had higher A than the abaxial side, but they showed similar values under saturating light. Although the abaxial leaf side was highly reflective, both surfaces presented the same response pattern for green light reflection, which can be explained by the compact spongy parenchyma observed in the leaves, increasing light use efficiency in terms of CO(2) consumption for paraheliotropic leaves. We propose that paraheliotropism in S. camporum is not related to leaf heat avoidance or photoprotection. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Abaxial and adaxial leaf surfaces; Cerrado; Light curves; Styracaceae